Studia ekonomiczne na Uniwersytecie Poznańskim, w latach 1919-1951 - Zakrzewski, Zbigniew (Wydział Prawa i Administracji UAM, 1970)
On account of 50th anniversary of the University of Poznań it is worth to remind the achievements of economical and political studies that had started at the University more than 25 years ago. In the past centuries Poznań and Great Poland were deeply interested in economical science and studies of economy at the university level. However only the foundation of the University of Poznań made possible the organization of economical and political studies. The aim of these studies was to prepare graduates for the needs of Polish economy and science, these graduates ought to be thoroughly prepared not only in general and theoretical basis of economy but also to think in terms of principles of other social sciences like law, administration and sociology. University training on the economical studies was to serve in preparation of graduates in managing and conceptional direction. The Economic and Political Section of the University of Poznań realized in the time of its existence 3-year studies and later 4-year studies. In the post-war period there were introduced new, obligatory subjects in the consequence of the new economic conditions in Poland and the needs of economy and plans. Among the lecturers of the Economical and Political Section of the University of Poznań were many meritorious scientifists. In the time of the existence of the Section there were given 56 doctor diplommas. Every third doctor chose the scientific carrier and worked in a high school. On the Economical and Political Section of the University studied average about 650 persons. The Section gave the finishing diplomas to about 1400 persons. Professors of the Section were very active in Poznań scientific and economical environment. The Economical and Political Section of the University of Poznań marked well in the history.
Economic Studies at Poznań University